A genome-wide association study of total child psychiatric problems scores - Neumann,A; Nolte,IM; Pappa,I; Ahluwalia,TS; Pettersson,E; Rodriguez,A; Whitehouse,A; van,Beijsterveldt CEM; Benyamin,B; Hammerschlag,AR; Helmer,Q; Karhunen,V; et al. (2020)
ABSTRACT Substantial genetic correlations have been reported across psychiatric disorders and numerous cross-disorder genetic variants have been detected. To identify the genetic variants underlying general psychopathology in childhood, we performed a genome-wide association study using a total psychiatric problem score. We analyzed 6,844,199 common SNPs in 38,418 school-aged children from 20 population-based cohorts participating in the EArly Genetics and Lifecourse Epidemiology (EAGLE) consortium. The SNP heritability of total psychiatric problems was 5.4% (SE=0.01) and two loci reached genome-wide significance: rs10767094 and rs202005905. We also observed an association of SBF2 , a gene associated with neuroticism in previous GWAS, with total psychiatric problems. The genetic effects underlying the total psychiatric problem score were shared with known genetic variants for common psychiatric disorders only (attention-deficit/hyperactivity disorder, anxiety, depression, insomnia) (r G > 0.49), but not with autism or the less common adult disorders (schizophrenia, bipolar disorder, or eating disorders) (r G < 0.01). Importantly, the total psychiatric problem score also showed at least a moderate genetic correlation of with intelligence, educational attainment, wellbeing, smoking, and body fat (r G > 0.29).The results suggest that many common genetic variants are associated with childhood psychiatric symptoms and related phenotypes in general instead of with specific symptoms. Further research is needed to establish causality and pleiotropic mechanisms between psychiatric disorders and related